Oral thin film: a review on orodispersible thin films for effective drug delivery of antiemetic drugs - Rahman, Md. Sazzad (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.